Strategies Coping for Female Detainee in Class IIA Women’s Correctional Institutions in Bandung - Rahayu, Mutia Sri; Yusuf, Ali Anwar; Achmad, Willya (PT ARRUS Intelektual Indonesia, 2023)
The purpose of this study was to determine the coping strategies and the results of coping strategies on problem focused coping and emotion focused coping used by female convicts in the Class IIA Women's Penitentiary in Bandung. This study used a qualitative approach with descriptive methods and used interviews, observation and documentation studies for data collection methods. The results of this study are first, the main cause of stress or stressor for prisoners is longing for family. Second, that prisoners more often use coping strategies on emotion focused coping, especially on positive reappraisal aspects as the main coping. Third, using problem focused coping on the aspect of seeking social support. Fourth, the results of using coping strategies are changes in their lives, they can live life better than before.